Descriptive Study of Academic Resilience of Students from Underprivileged Families - Pratiwi, Annisa Jodi; Netrawati, Netrawati (Universitas Negeri Padang, 2025)
This research is motivated by cases found in students who come from underprivileged families want to continue and complete their studies. Seeing the conditions of students who come from underprivileged families and schools make policies that provide school assistance to underprivileged students. This study aims to describe the description of academic resilience in SMA 12 Padang students. The research method used is descriptive quantitative research method. The sample in this study were 109 students at SMA 12 Padang who were selected using purposive sampling technique. Data were collected by providing research instruments in the form of a Likert model measuring scale. The overall picture of academic resilience of SMAN 12 Padang students is in the high category with a frequency of 83 students with a percentage of 76.14% of the total sample. This illustrates that students' academic resilience tends to be high which can be described from the existing aspects. As in the confident aspect, control aspect, composure aspect, and commitment aspect.